Greening the existing building (Chancellery Building - Universiti Teknikal Malaysia Melaka) - Al-Ani, Mustafa Khudhur Hussein (2016)
Buildings contribute significantly to the environmental and economic issues, as they consume a high amount of energy and water. As a building consumes energy, it contributes to emissions of carbon dioxide which lead to environmental pollution. These factors have a negative impact on the environment and the economy among other issues. Green building practices and approaches can considerably reduce or eliminate negative ecological and economic impacts. This study aims to "greening the existing building" (Chancellery Building - University Teknikal Malaysia Melaka) and achieve the "Certified" rating level according to the GBJ classification, taking into consideration estimated cost. The green building audit results show the total current building rating level is only 18 off I 00 points based on the major six criteria. Including Energy Efficiency (EE), Indoor Environment Quality (EQ), Sustainable Site Planning & Management (SM), Materials & Resources (MR), Water Efficiency (WE), and Innovation (IN), this shows the existing Chancellery building achieves a low rating level when evaluated according to the GBI rating system. To achieve a "Certified Rating Level" of (50 points) this study proposes improvements of existing building's criteria (Retrofitting). The economic analysis involves the estimation of costs included in "Greening Existing Building" and the potential savings acquired from "Retrofitting". The estimated cost of greening the proposed building is RM 800,764. This demonstrates the "Greening Existing Building" requires several improvements aspects which are considered very costly to attain. Additionally, the potential savings includes cutting costs from Lighting System and Building Integrated Photo Voltage. The potential savings from Lighting System is (67345.9 RM/year) and the payback period is (1.68 years). Also, the potential saving from Building Integrated Photo Voltage is (30492RM/year) and the payback period is (4.9 years).